Cardiac-Restricted IGF-1Ea Overexpression Reduces the Early Accumulation of Inflammatory Myeloid Cells and Mediates Expression of Extracellular Matrix Remodelling Genes after Myocardial Infarction - Enrique Gallego-Colon; Robert D. Sampson; Susanne Sattler; Michael D. Schneider; Nadia Rosenthal; Joanne Tonkin (Mediators of Inflammation)
Strategies to limit damage and improve repair after myocardial infarct remain a major therapeutic goal in cardiology. Our previous studies have shown that constitutive expression of a locally acting insulin-like growth factor-1 Ea (IGF-1Ea) propeptide promotes functional restoration after cardiac injury associated with decreased scar formation. In the current study, we investigated the underlying molecular and cellular mechanisms behind the enhanced functional recovery. We observed improved cardiac function in mice overexpressing cardiac-specific IGF-1Ea as early as day 7 after myocardial infarction. Analysis of gene transcription revealed that supplemental IGF-1Ea regulated expression of key metalloproteinases (MMP-2 and MMP-9), their inhibitors (TIMP-1 and TIMP-2), and collagen types (Col 1α1 and Col 1α3) in the first week after injury. Infiltration of inflammatory cells, which direct the remodelling process, was also altered; in particular there was a notable reduction in inflammatory Ly6C+ monocytes at day 3 and an increase in anti-inflammatory CD206+ macrophages at day 7. Taken together, these results indicate that the IGF-1Ea transgene shifts the balance of innate immune cell populations early after infarction, favouring a reduction in inflammatory myeloid cells. This correlates with reduced extracellular matrix remodelling and changes in collagen composition that may confer enhanced scar elasticity and improved cardiac function.